Best Practices in Evaluating Cervical Spine Injury - Cunningham, Muriel (MD Conference Express, 2014)
Trauma patients must be evaluated for spinal injuries in an efficient manner. However, cervical spine (C-spine) imaging can be time-consuming, costly, and painful, and exposes the patient to radiation. This article reviewS current strategies to optimize decision making when evaluating patients with possible C-spine injuries.